2‐(1‐Benzotriazolyl)pyridine: A Robust Bidentate Ligand for the Palladium‐Catalyzed CC (Suzuki, Heck, Fujiwara–Moritani, Sonogashira), CN and CS Coupling Reactions. Issue 2 (1st February 2013) - Verma, Akhilesh K.; Jha, Rajeev R.; Chaudhary, Ritu; Tiwari, Rakesh K.; Danodia, Abhinandan K.
Abstract A new class of bidentate ligand, 1‐(pyridine‐2‐yl)‐1H‐benzo[d][1, 2, 3]triazole has been designed and employed for the palladium‐catalyzed CC (Suzuki, Heck, Fujiwara–Moritani, and Sonogashira), CN and CS coupling reactions. The ligand was found to be inexpensive, thermally stable, easy to synthesize from easily accessible starting materials on a multigram scale, show simplicity in use, and robustness in application, making this ligand effective for different coupling reactions. Suitably, the donor ability of the NN bond of the benzotriazole ring and lone pair of electrons on the N of the pyridine ring enhance the bidentate ability of the ligand.